The benefits of information communication technology use by the homeless: a narrative synthesis review. Issue 1 (March 2014) - Sala, Adrien; Mignone, Javier
<x content-type="archive" xml:space="preserve">Abstract</x> Recent studies have suggested that technologies are becoming an increasingly ubiquitous element in the lives of individuals experiencing homelessness. With both Canadian and US researchers reporting staggering levels of homelessness on both sides of the border, an understanding and synthesis of the current literature exploring how technologies are being utilized by homeless individuals and how it may impact their well-being is of relevance to policy makers and social service organizations. The study explored and synthesized literature to examine the ways in which individuals experiencing homelessness utilize information and communication technologies (ICTs), and how the use of ICTs influences the health and social outcomes of individuals experiencing homelessness. The study examined 16 peer reviewed articles using a narrative synthesis systematic review, following three elements of the narrative synthesis approach: preliminary synthesis of findings; exploration of relationships between studies; and assessment of the robustness of the synthesis. In relation to what ICTs are used for by homeless individuals, three major themes emerged: social connectedness, identity management, and instrumental purposes. Furthermore, there was some tentative evidence about a positive relationship between ICT use among individuals experiencing homelessness and health outcomes. The paper discussed limitations, future areas of research, as well as some policy directions.